The Salonika trial: Political retribution against Serbian patriotic movement - Gaćinović Radosav (NBP: Nauka, bezbednost, policija, 2016)
The Salonika Trial ended before the Great Military Court at the beginning of June 1917, and the judgment was passed on June 05, 1917. Seven defendants were sentenced to death: Colonels Dragutin Dimitrijević Apis, Milan Gr. Milovanović, Radoje Lazić, Vladimir Tucović, Lieutenant-Colonel Velimir Vemić, Majors Ljubomir Vulović and Rade Malobabić. Colonel Čedomir Popović, Vice-consul Bogdan Radenković, retired General Damjan Popović and Muhamed Mehmedbašić were sentenced to twenty years in prison. The Prince Regent commuted the death sentence for Lazić, Milovanović, Popović and Mehmedbašić to twenty years in prison, and to ten years in prison for Vice-consul Radović. Of all defendents Colonel Dragutin Dimitrijević Apis, Major Ljubomir Vulović and Rade Malobabić were executed by firing squad at the Salonika field on June 26, and their bones were later brought over to Zeitenlik and buried in the cases with nameless cover plates. Late in 1952 Aleksandar Ranković got a letter which Major Ljubomir Vulović, sentenced in the Salonika trial, sent on June 12, 1917 (before his execution by firing squad) via military priest Zdravko Paunović to his friend Todor Mihailović, a retired teacher who lived in Belgrade at that time. In his letter Major Vulović wrote that he and his friends were sentenced although they were innocent, that the first time he had heard about the assassination attempt on the then Prince Regent Aleksandar was during the hearing and that the orchestrators of the Salonika process used false witnesses. In the same letter Major Vulović pleaded to determine the real truth in the liberated homeland and to clear the names of those convicted and executed. Acting upon the wish of Major Vulović, and pursuant to the order of Aleksandar Ranković, the Investigation unit tracked the two main witnesses for the assassination attempt, Temeljko Veljanović (then Temelko Veljanovski), the President of the municipality in the village of Novaci for many years after the First World War, and Djordje Konstantinović (then Georgi Konsantinovski), the President of the Municipality in the village of Brod after the First World War. Once witnesses at the Salonika trial, Temeljko Veljanović and Djodje Konstantinović gave statements on January 29, 1953, confirming before the judge of the County Court in Bitol their recorded statements that in the Salonika military prison in 1917 under threat of death they were coerced to give false testimony and to incriminate the defendants Rade Malobabić, Muhamed Mehmedbašić and Major Ljubomir Vulović. Further investigation led to the information based on which it could be concluded that 1917 Salonika Trial was orchestrated at the order of the Prince Regent Aleksandar and the Prime Minister Nikola Pašić, and that it was staged by the then Commander of the Palace Guards Colonel Petar Živković and the Minister of Interior Ljuba Jovanović, called the Duck, with his police apparatus. Based on the evidence and other material collected, as well as the proposal of the Public Prosecutor of Serbia, the Supreme Court of Serbia found there was place to renew the Salonika trial, and based on the 1948 Law on Criminal Procedure, held a new trial to the defendants in the Salonika process in the period from June 2 to 13, 1953, in Belgrade. The judgment by which all defendants were exonerated in the Salonika trial was announced on June 16, 1953.